Analysis of Healthcare Resource Utilization and Costs after the Initiation of Biologic Treatment in Patients with Ulcerative Colitis and Crohn’s Disease - Sue Perera; Shibing Yang; Marni Stott-Miller; Joanne Brady (Journal of Health Economics and Outcomes Research)
**Background:** This retrospective cohort study aimed to describe and quantify healthcare resource utilization and costs for patients with ulcerative colitis (UC) and Crohn’s disease (CD) following initiation of biologic therapy.